Extranodal Rosai–Dorfman Disease as Isolated Lesion of the Tibia Diagnosed by Fine-Needle Aspiration Cytology: A Case Report. Issue 47 (November 2015) - Xu, Jie; Liu, Chun-Hua; Wang, Yan-Si; Chen, Chang-Xian
Abstract : Abstract: Few studies have used fine-needle aspiration cytology for the purpose of isolated skeletal Rosai–Dorfman diseases (RDDs) diagnosis. Herein, we described an extremely rare case of a 56-year-old woman who presented to our hospital with an insidious onset of pain in the right proximal tibia. The provisional cytologic diagnosis of RDDs was confirmed by a computer tomography-guided core needle biopsy of the lesion. Subsequently, curettage and autogenous iliac crest bone graft were performed successfully. At the 4th year of follow-up her clinical symptoms disappeared, and there was no clinical evidence of lesion recurrence. Our case highlighted the role of fine-needle aspiration cytology with immunohistochemical studies in the diagnosis of RDDs and the characteristic features of isolated skeletal RDDs in an unusual location, the knowledge of which would help avoid missed or delayed diagnosis in the future.